Britain and the confrontation with Indonesia, 1960-66 - Easter, David (Tauris Academic Studies, 2004)
The confrontation with Indonesia cut to the heart of Britain's desire to retain global power status in the 1960s and was central to decolonisation and British defence policy across South-East Asia. Factors such as the need to maintain a military base in Singapore drove strategy and this confrontation became a major commitment - close at times to escalating into full-scale regional war. However, 'the Confrontation' was not recorded as a conflict of this scale, and Britain was cast into a passive and defensive role. Here, David Easter reveals a radically different view, persuasively making the c.